Plug the gap: Make resolution ready for corona - Thomas F. Huertas (Leibniz Institute for Financial Research SAFE, 2020)
Banks are not immune from COVID-19. The economic downturn may drive some banks to the point of non-viability (PONV). If so, is the resolution regime in the Euro-area ready to respond? No, for banks may not have the right amount of the right kind of liabilities to make bail-in work. That could lead to a banking crisis. The Euro area can avoid this risk, by arranging now for a recap later. This would plug the gap between what the failing bank has and what it would need to make bail-in work. To do so, banks would pay - possibly via the contributions they make to the Single Resolution Fund - a commitment fee to a European backstop authority for a mandatory, system-wide note issuance facility. This would compel each bank, as it approached or reached the PONV, to issue to the backstop, and the backstop to purchase from the bank, the obligations the failing bank needs in order to make bail-in work. Such obligations would take the form of "senior-most" non-preferred debt, and bail-in would stop with such debt. That would allow the SRB to use the bail-in tool to resolve the failed bank, reopen it and run it under a solvent wind-down strategy. That protects counterparties and customers and ensures the continuity of critical economic functions. It also keeps investors at risk and promotes market discipline. Above all, it preserves financial stability.
Keywords: 330; Resolution; Covid-19; Banking Crisis